Antithrombotic Therapy With Ticagrelor in Atrial Fibrillation Subjects After Percutaneous Coronary Intervention - Lu, Wenbin; Wang, Yu; Chen, Lijuan; Li, Yongjun; Zhang, Rui; Chen, Zhongpu; Yan, Jinchuan; Yang, Mingming; Han, Bing; Wang, Zhirong; He, Shenghu; Chen, Lianglong; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Warfarin, along with aspirin and clopidogrel, has long been recommended for patients with atrial fibrillation (AF) who are undergoing percutaneous coronary intervention with a drug-eluting stent (PCI-ES). However, this triple therapy has been known to increase the risk of bleeding complications. We here aimed to compare the antiplatelet drug ticagrelor as a dual antithrombotic agent to aspirin and clopidogrel in bleeding events. Methods: In this multicenter, active-controlled, open-label, randomized trial, patients with AF taking warfarin who had undergone PCI-ES were randomly assigned to the ticagrelor therapy group (Dual group) or the clopidogrel plus aspirin therapy group (Triple group). The primary and secondary endpoints were overall bleeding events and major bleeding events, respectively, according to the Thrombolysis in Myocardial Infarction (TIMI) criteria at 6 months. Cardiovascular events (re-PCI, surgical bypass, myocardial infarction (MI), heart failure, rehospitalization due to angina pectoris, stent thrombosis and death due to cardiovascular causes) at 6 months were also recorded. Results: A total of 296 patients from 12 medical centers in China were randomized to either the Dual therapy group (n=148) or the Triple group (n=146). The overall incidence of bleeding events at 6 months was 36.49% in the Dual therapy group and 35.62% in the Triple group (hazard ratio, 0.930; 95% confidence interval [CI], 0.635 to 1.361; P = 0.7088). The incidence of the secondary endpoint over 6 months was 4.73% in the Dual therapy group and 1.37% in the Triple group (hazard ratio, 0.273; 95% CI, 0.057 to 1.315; P = 0.1056). Cardiovascular event occurrence was also comparable in both groups at 6 months (18.24% vs. 16.44%; hazard ratio, 0.845; 95% CI, 0.488 to 1.465; P = 0.5484). Conclusions: The incidence of total bleeding events in AF patients treated with ticagrelor was comparable to that in patients treated with clopidogrel plus aspirin without an increased risk of ischemic events.